Enhancing particle swarm optimization based on optical computing mechanism: application to dyslexia detection - Mahmoud, Nermine; Abd Elaziz, Mohamed; Dahou, Abdelghani; Ghatasheh, Mohammad; Fares, Ibrahim A.; Al-Betar, Mohammed Azmi; Ewees, Ahmed A. (Frontiers in Artificial Intelligence, 2026)
IntroductionThis study presents a modified version of Particle Swarm Optimization (PSO) using an all-optical computational update mechanism. The primary innovation and objective of this collaboration aimed to leverage the inherent properties of coherent optical systems, including specialized complex-domain computation and nonlinear light-matter interactions, to enhance the exploration and exploitation of the search space process for particles.MethodsTo assess the performance of the developed model, it was compared with traditional PSO to solve the CEC benchmark functions. Furthermore, it was applied to enhance the detection of dyslexia using the eye-tracking dataset (ETDD).ResultsThe comparison between OPSO and other techniques established its high ability to enhance the detection of dyslexia over traditional techniques.DiscussionThe use of an all-optical computational update mechanism demonstrated enhanced performance in both benchmark optimization problems and dyslexia detection tasks.